2020
DOI: 10.3390/ijerph17207388
|View full text |Cite
|
Sign up to set email alerts
|

Does Severity of Hair Loss Matter? Factors Associated with Mental Health Outcomes in Women Irradiated for Tinea Capitis in Childhood

Abstract: Hair loss resulting from childhood irradiation for tinea capitis has been linked to mental health effects in women. However, the association of hair loss severity with mental health in this population is unknown. To address this gap, this study examined the association between hair loss severity and mental health outcomes in women irradiated for tinea capitis in childhood as well as the factors that contribute to these outcomes. Medical records, held at the archives of the Israel National Center for Compensati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…These results clearly suggest that the gender difference in depression risk is not due to the higher prevalence of other risk factors among women, such as low self-esteem, social anxiety, and social avoidance, but rather due to the effect of gender per se. By shedding light on the role of gender in the development of depression among women with alopecia resulting from childhood irradiation for tinea capitis, our results add to earlier reports documenting depression among women with different types of alopecia [32,35,[46][47][48] and higher rates of depression among women with androgenetic alopecia compared to men [24]. A plausible explanation for the important role that gender plays in the development of depression among women with alopecia is that hair symbolizes women's fertility, femininity, sexuality, and attractiveness in society [7,9,10].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…These results clearly suggest that the gender difference in depression risk is not due to the higher prevalence of other risk factors among women, such as low self-esteem, social anxiety, and social avoidance, but rather due to the effect of gender per se. By shedding light on the role of gender in the development of depression among women with alopecia resulting from childhood irradiation for tinea capitis, our results add to earlier reports documenting depression among women with different types of alopecia [32,35,[46][47][48] and higher rates of depression among women with androgenetic alopecia compared to men [24]. A plausible explanation for the important role that gender plays in the development of depression among women with alopecia is that hair symbolizes women's fertility, femininity, sexuality, and attractiveness in society [7,9,10].…”
Section: Discussionsupporting
confidence: 75%
“…The first study [32] found that hair loss due to childhood irradiation for tinea capitis in women is linked to psychosocial impacts, including depression, anti-depressant and/or anti-anxiety drug use, psychiatric hospitalization, suicide attempts, social anxiety, and divorce, as well as health impacts, such as migraines, which have been found to be associated with childhood trauma and stressful life events in adulthood [33,34]. The second study [35] extended these findings, linking hair loss severity in women to an increased risk of mental health problems and showing an indirect effect of hair loss severity on mental health via an impact on women's social life. To date, no study has investigated the effects of hair loss in men irradiated for tinea capitis during childhood or examined gender differences in the outcomes of hair loss resulting from childhood irradiation for tinea capitis.…”
Section: Introductionmentioning
confidence: 99%
“…The ringworm claimants’ mistrust in Israeli healthcare organizations might, in addition to the lack of a clear notification process, also be partly explained by the emotional influences of such treatments [ 47 ], legal claims against the Israeli government based on the duty to inform patients at risk [ 43 ], and a reluctance of the Israeli Authorities to publish a formal apology for implementing the treatment regime [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hair is an important part of human body, but hair loss has been a global public health problem that is mainly related to the aging process. Various factors can cause hair loss, including mental stress, disease, autoimmune diseases, and drug treatments [1,2]. The main cause of hair loss, especially in men, is attributed to a decrease in male hormones.…”
Section: Introductionmentioning
confidence: 99%